FOXG1 Syndrome: Unraveling Congenital Rett-Like Disorder: FOXG1 Syndrome - Balakumaran, Parasuraman; Jeet Daniel, Nivya; Rajan, Nishanth; Kumar Kommu, Peter Prasanth (International Clinical Neuroscience Journal, 2026)
FOXG1 syndrome is a rare neurodevelopmental disorder caused by mutations in the FOXG1 gene, leading to severe developmental delay, microcephaly, movement disorders, epilepsy, and autistic features. Though it shares some phenotypic similarities with Rett syndrome, it has a distinct genetic etiology and clinical course. We report a 1-year-old 3-month-old boy, the second-born child of a non-consanguineous couple, who presented with recurrent seizures from 4 months of age, characterized by infantile spasms. The child exhibited global developmental delay, poor social interaction, irritability, and sleep disturbances. Clinical examination revealed microcephaly, hypotonia, exaggerated deep tendon reflexes, and extensor plantar responses. Neuroimaging showed benign enlargement of the subarachnoid space, and genetic testing confirmed a pathogenic FOXG1 mutation. Despite multiple anti-seizure medications, the child’s epilepsy remained refractory. He is currently being managed on a ketogenic diet, anti-epileptic medication, and intensive multidisciplinary therapy sessions. This case highlights the diagnostic challenges of FOXG1 syndrome and its overlapping but distinct features from Rett syndrome. The patient’s refractory epilepsy, severe developmental delay, and poor response to conventional therapies align with existing literature. Neuroimaging findings in these patients are varied. This syndrome has a poor prognosis, with no definitive treatment available at present. FOXG1 syndrome is a distinct entity requiring early diagnosis and multidisciplinary management. Further research into gene-targeted therapies is crucial for improving outcomes.